CLINICAL AND LABORATORY FEATURES OF CARDIORENAL SYNDROME IN PATIENTS WITH DIABETES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Violation of the kidney filtration function is common enough among patients with cardiovascular disease (CVD), especially against disorders of carbohydrate metabolism (IGM). Renal dysfunction (PD) is associated with more frequent development of cardiovascular complications. In turn, the probability of the development of renal disease in patients with cardiovascular disease is significantly higher than in the general population. These bidirectional pathogenetic mechanisms existing between cardiovascular and kidney diseases were the basis for the formation of the cardiorenal syndrome concept. The review discusses the general parts of pathogenesis within the cardiovascular continuum. In addition, it shows the effect on metabolic disorders during CVD combined with renal dysfunction. The review reveals a recent view on the main mechanisms of cardiorenal syndrome.